Measuring crime: Methodological considerations on recording and interpreting crime statistics in local - national, European and international levels - Tsiganou, Joanna; Dendrinou, Chrysoula; Iliou, Catherine; Roinioti, Eleni (The Greek Review of Social Research, 2014)
The scope of this paper, is to provide a starting point for discussion and sharing of our understandings of crime statistics for the use in both, local-national levels and comparatively.